A Scope of Implementation intellectual Capital Accounting and Supply Chain Management in Telecommunication Companies: Evidence from Iraq - Awad, Saad Salman; Mohammed Wathik, Ilham; Khadim Hussein, Ali (International Journal of Supply Chain Management, 2019)
Research positioned in the intersection between management accounting and supply chain management is increasing. So, the core purpose of this research study is to identify the range of harmonization between theoretical concepts of Intellectual Capital (IC) around the three aspects and empirical practices required from international and local accounting standards (IAS). The current research follows the positivist paradigm and quantitative in nature. Secondary data was used to measure the compatibility between the theoretical concepts of intellectual capital and the items that were accepted in international accounting standards across ratios, and to test these variables with TIST between the average actual practices of companies and the objective value (theoretical concepts of intellectual capital). The items will later include the items in the International Accounting Standards and the actual practices of telecommunications companies in Iraq. The results show that there are significant differences between the theoretical concepts of IC in International Accounting and Reporting Standards - IAS 38. The areas where there is no match related to items that do not meet the condition of the concept of assets or do not achieve the rules of proof of accounting or measured to be reliable. The results were derived from the analysis of the financial statements of Zain and Asia Cell and its annual reports, including analytical tables and explanatory notes. The confidentiality of some data related to the work of companies is one of the difficulties of conducting such research, as some of these data are linked to the competitiveness of companies and tax matters, as well as the lack of companies operating in this sector in Iraq. This research is the first modest attempt on social environment of Iraqi knowledge economy, which represents telecommunications companies one of its components and associated components of intellectual capital. This study makes a contribution to the literature by conceptualizing the elements of management accounting in a context of the supply chain and by relating it to supply chain strategy and supply chain relationship structure.